BIOMONITORING: SEBAGAI ALAT ASESMEN KUALITAS PERAIRAN AKIBAT LOGAM BERAT KADMIUM PADA INVERTEBRATA PERAIRAN - Dominggus Rumahlatu (Lembaga Penelitian dan Pengembangan Universitas Islam Negeri Maulana Malik Ibrahim Malang., 2011)
People’s activity in water area has made this area as waste place from a variety of human’s activity. One contaminant thrown to the seaboard is heavy metal, specifically for cadmium (Cd). Naturally, the pollution sources of heavy metal Cd in water area are coming from geological process and some of human’s activity (antropogenic). The effect of Cd’s contamination to invertebrate water are died effect and ecology’s unbalancing of sea organism varieties. It is because Cd cannot be broken up (non degradable) by living organism and it can be accumulated to the environment. One effort to tackling heavy metal Cd contamination in water is doing biomonitoring accumulation as assessment instrument of water quality.Key words: biomonitoring, biomoitoring accumulation, heavy metal Cadmium, invertebrate water